Mentorship model for the development of environmental culture in future fashion designers - Ratii, Alina (Педагогічна Академія: наукові записки, 2025)
Current trends in globalized societal development determine the need for integrating the environmental component into the system of professional training for specialists in the fashion industry, which belongs to the environmentally sensitive sectors of the economy. The formation of environmental culture among future fashion designers is a key factor in ensuring their ability to implement the principles of sustainable design and environmentally responsible production. Mentorship is considered an effective pedagogical technology that combines the individualization of the educational process with the development of professionally significant values and environmental awareness. The purpose of the study is to scientifically substantiate and experimentally verify the effectiveness of a pedagogical mentorship model aimed at developing the environmental culture of future fashion designers during their professional training. Methods. The methodological basis of the study combines competence-based, activity-based, and structural-functional approaches. Methods of analysis, synthesis, and generalization of scientific sources were applied; pedagogical modeling was used to design the mentorship model; questionnaires, expert evaluations, and a pedagogical experiment were employed to assess the effectiveness of the implemented pedagogical solutions. Results. The developed mentorship model includes motivational value, cognitive, and operational-activity components integrated into a single pedagogical system. A methodological toolkit for mentorship interaction was proposed, which provides for the implementation of environmental design, the use of environmentally friendly materials, the organization of creative workshops, and case methods aimed at solving environmental problems in design. Conclusions. The integration of mentorship into the educational process of fashion designer training ensures the formation of a holistic environmental culture, the development of professional environmental competence, and the establishment of stable value orientations necessary for implementing the concept of sustainable development in the fashion industry. Further research should focus on adapting the model to various levels of vocational education and international educational standards.